2016
DOI: 10.3390/microorganisms4040042
|View full text |Cite
|
Sign up to set email alerts
|

Dirty Money: A Matter of Bacterial Survival, Adherence, and Toxicity

Abstract: In this study we report the underlying reasons to why bacteria are present on banknotes and coins. Despite the use of credit cards, mobile phone apps, near-field-communication systems, and cryptocurrencies such as bitcoins which are replacing the use of hard currencies, cash exchanges still make up a significant means of exchange for a wide range of purchases. The literature is awash with data that highlights that both coins and banknotes are frequently identified as fomites for a wide range of microorganisms.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 34 publications
3
23
0
2
Order By: Relevance
“…Humid conditions improved persistence for most types of bacteria, such as Salmonella typhimurium, P. aeruginosa, E. coli or other relevant pathogens [2,9,21,25]. In previous studies, reported that Enterobacteraceae members are 13%-55.5% range of the paper currencies and the most frequently isolated enteric bacteria was E. coli (19.4-48.14%) [2,3,9]. Antimicrobial resistance is a global phenomenon that has resulted in high morbidity and mortality as a result of treatment failures and increased health care costs.…”
Section: B) Molecular Detection Of Ses Pvl and Tsst -1 Genesmentioning
confidence: 96%
See 3 more Smart Citations
“…Humid conditions improved persistence for most types of bacteria, such as Salmonella typhimurium, P. aeruginosa, E. coli or other relevant pathogens [2,9,21,25]. In previous studies, reported that Enterobacteraceae members are 13%-55.5% range of the paper currencies and the most frequently isolated enteric bacteria was E. coli (19.4-48.14%) [2,3,9]. Antimicrobial resistance is a global phenomenon that has resulted in high morbidity and mortality as a result of treatment failures and increased health care costs.…”
Section: B) Molecular Detection Of Ses Pvl and Tsst -1 Genesmentioning
confidence: 96%
“…can survive on inanimate surfaces even for months. Overall, Gram-negative bacteria have been described to persist longer than Gram-positive bacteria [3,21]. Humid conditions improved persistence for most types of bacteria, such as Salmonella typhimurium, P. aeruginosa, E. coli or other relevant pathogens [2,9,21,25].…”
Section: B) Molecular Detection Of Ses Pvl and Tsst -1 Genesmentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro culture studies have established that paper currency can harbor high levels of microbes, some of which are clinically significant, such as the causative agents of pneumonia and enteric diseases [1820], and various antibiotic resistant strains [21]. Laboratory simulations also provide evidence that many microorganisms can survive on office paper [22], coins [23] and banknotes of various materials [19, 24]. These studies, though limited, have established that microbial contamination of paper currency is widespread, and that money represents an important human-microbe interface.…”
Section: Introductionmentioning
confidence: 99%